Saiga horn user characteristics, motivations, and purchasing behaviour in Singapore - Doughty, H; Veríssimo, D; Tan, R; Lee, J; Carrasco, L; Oliver, K; Milner-Gulland, E (Public Library of Science, 2019)
Unsustainable wildlife trade is a pervasive issue affecting wildlife globally. To address this issue, a plethora of demand reduction efforts have been carried out. These necessitate consumer research which provides crucial knowledge for designing and evaluating targeted interventions. We implemented a rigorous consumer survey on saiga (Saiga tatarica) horn use in Singapore, where usage is legal and widely sold. Saiga are Critically Endangered antelopes from Central Asia with horns (often marketed as ling yang) used in traditional Chinese medicine (TCM). Few past studies have assessed saiga horn consumers. This work is the most extensive consumer research to date specifically characterising saiga horn consumers and usage. We conducted 2294 in-person surveys on saiga horn use with Chinese Singaporeans, employing neutral questioning approaches. We found 19% of individuals reported saiga horn as a product they choose most often for themselves and/or others when treating fever and/or heatiness (a TCM state of illness), indicating a minimum estimate of high-frequency usage, not including possible low-frequency users. Overall saiga users were most characterised as middle-aged Buddhists and Taoists. However, saiga users were found in a range of demographic groups. Women preferred saiga shavings (the more traditional form), while men preferred saiga cooling water (the more modern form). About 53% of individuals who used saiga horn themselves also bought it for someone else. Buyers for others were most likely to be female middle-aged Buddhists or Taoists. Key motivating reasons for usage were “it works” and “someone recommended it to me.” The top two reported recommenders were family and TCM shopkeepers. Saiga users were more likely than non-saiga users to perceive saiga as a common species in the wild. This research holds significance for interventions targeting saiga horn consumption within Singapore and throughout Asia, by identifying potential target audiences, product types, non-desirable alternatives, and motivations for use.